STATUS GIZI IBU HAMIL DAN KAITANNYA DENGAN BERAT DAN PANJANG BAYI LAHIR - Rarastiti, Chaerunisa Nur (Indonesian Journal of Nutrition Science and Food; Vol 1 No 2 (2022): Januari 2022, 2022)
Improving the quality of human resources is one of national development goals. Those efforts can be made with fulfillment of nutritional needs that begins from pregnancy. This study aimed to analyze the relationship between maternal nutritional status with weight and length of birth. This study is a retrospective cohort with 40 pregnant women in Gunung Geulis Village, Sukaraja Subdistrict-Bogor District. Primary data collected by using questionnaire, maternal mid upper arm circumference (MUAC) and height by anthropometric measurements. Maternal weight gain, weight and length of birth based on KIA book. Data were analyzed using Pearson and Spearman correlation test. The results showed that 25% mothers with MUAC <23.5 cm and 25% mothers with weight gain <9 kg. While 30% infants with birth weight 2500-2999g and 5% with birth length <48 cm. There were a relationship between maternal MUAC with birth weight (p=0.002; r=0.479) and birth length (p=0.027; r=0.349), also maternal weight gain with birth weight (p=0,039; r=0.327). A significant positive correlation indicates that maternal MUAC and weight gain during pregnancy are factors that affect weight and length of birth in the research area.